The return of the Indian - Lynne Reid Banks (New York Avon Camelot, 1993)
"The Return of the Indian" by Lynne Reid Banks is a captivating children's fantasy novel and a sequel to "The Indian in the Cupboard." The story follows Omri, who has the power to bring plastic toys to life through a magical cupboard. In this installment, Omri, along with his friend Patrick, embarks on a new adventure when they decide to return to the magical world of Little Bear, a Native American Indian.
Keywords: Children's literature; Fantasy